2007
DOI: 10.1002/anie.200700765
|View full text |Cite
|
Sign up to set email alerts
|

A Long Research Story Culminates in the First Total Synthesis of Moenomycin A

Abstract: The highly active inhibitor of the “forgotten” transglycosylases, moenomycin A, succumbed to total synthesis. The pentasaccharide backbone was constructed employing sulfoxides as glycosyl donors. The recent moenomycin results should establish it as a promising lead structure for new antiinfectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Only recently have these challenges been surmounted, culminating after decades of effort in the first total synthesis of 1 (Scheme 3). This achievement, in conjunction with the aforementioned moenomycin degradation-reconstruction approach, deploys a powerful toolkit for chemical synthesis of different types of moenomycin fragments and analogs 60, 99, 100…”
Section: Moenomycins As a Target Of Chemical Synthesis And Degradatmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently have these challenges been surmounted, culminating after decades of effort in the first total synthesis of 1 (Scheme 3). This achievement, in conjunction with the aforementioned moenomycin degradation-reconstruction approach, deploys a powerful toolkit for chemical synthesis of different types of moenomycin fragments and analogs 60, 99, 100…”
Section: Moenomycins As a Target Of Chemical Synthesis And Degradatmentioning
confidence: 99%
“…This achievement, in conjunction with the aforementioned moenomycin degradation-reconstruction approach, deploys a powerful toolkit for chemical synthesis of different types of moenomycin fragments and analogs. 60,99,100 The oligosaccharide portion of 1 was entirely constructed using sulfoxide glycosylation chemistry, 101,102 although multiple adjustments to (and modifications of) the standard procedure had to be made to stereoselectively generate several of the linkages. 99 The pentasaccharide was built in a modular manner in which disaccharides BC and EF were produced first, then the CE bond was formed between the disaccharides to give the BCEF tetrasaccharide.…”
Section: The Total Synthesis Of Moenomycin Amentioning
confidence: 99%
“…Crystal structures of several different PGTs containing MoeA have been reported and show that the compound binds in the same region of the active site where the elongating polymer binds (1922). The antibiotic activity of MoeA has been attributed to PGT inhibition (2324), although no resistant mutants containing PGT substitutions have been previously identified to confirm this mechanism (17). In fact, no specific mechanisms for MoeA resistance have been described, although it was suggested that upregulation of PBP genes may help overcome MoeA inhibition (25).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, Moe A is the most abundant agent in its family (3,4). The unique antibacterial properties of Moe A have prompted chemists to synthesize moenomycin fragments and derivatives (5)(6)(7) in an attempt to develop new antibiotics. Recently, the total synthesis of Moe A (8), and of its biosynthesis pathway (9), has been reported.…”
mentioning
confidence: 99%